(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
Studies on the ecology and abundance of Bellamya bengalensis (Lamarck, 1822) was carried out in Rajshahi University Campus in pond habitat. The physico-chemical parameters viz. water temperature (27.6 ± 4.23 °C in 1995 and 27.4 ± 4.43 °C in 1996), water transparency (0.41± 0.03 cm in 1995 and 0.42 ± 0.04 cm in1996), sunshine (6.22 ± 1.98 hours in 1995 and 7.41 ± 1.56 hours in 1996), pH (7.78 ± 0.38 in 1995 and 7.84 ± 0.27 in 1996), DO (4.92 ± 0.75 mg/l in 1995 and 5.73 ± 1.5 mg/l in 1996) and CO2 (5.45 ± 2.06 mg/l in 1995 and 4.04 ± 1.34 mg/l in 1996) of different ponds were recorded.The physico-chemical parameters viz. water temperature (25.82 ± 4.87 °C in 1995 and 25.96 ± 5.4 °C in 1996), water transparency (0.37 ± 0.02 cm in 1995 and 0.4 ± 0.03 cm in 1996), pH (7.78 ± 0.08 in 1995 and 7.8 ± 0.12 in 1996), DO (3.1 ± 0.06 mg/l in 1995 and 2.86 ± 0.31mg/l in 1996) and CO2 (14.6 ± 0.76 mg/l in 1995 and 13.54 ± 1.53 mg/l in 1996) of ditches were recorded. The physico-chemical parameters viz. water temperature (30.18 ± 1.21 °C in 1995 and 30.07 ± 1.21 °C in 1996), pH (7.93 ± 0.3 in 1995 and 7.98 ± 0.3 in 1996), DO (4.93 ± 0.12 mg/l in 1995 and 4.97 ± 0.13 mg/l in 1996) and CO2 (5.63 ± 1.74 mg/l in 1995 and 5.57 ± 1.78 mg/l in 1996) of irrigated paddy field were determined. The rainfall was recorded as 123.36 ± 127.27 cm and 105.75 ± 111.11 cm during 1995 and 1996, respectively. Thirty five spp. of hydrophytes were identified. The minimum and maximum abundances per m2 were determined as 124.58 ± 58.93 and 133.33 ± 60.84 during the observation periods of 1995 and 1996, respectively. Bangladesh J. Sci. Ind. Res. 52(2), 107-114, 2017